Pengaruh Strategi Pemasaran Terhadap Minat Nasabah Pada PT.Bank Tabungan Negara (Persero) Tbk Kantor Cabang Ambon - Christin M Leuhena; Maudy Marla Tanihatu; Saul Ronald Jacob Saleky (P3M Politeknik Negeri Ambon, 2023)
This research was conducted to examine the marketing strategies of BTN Bank Ambon Branch Office in attracting customers to saving money. The research to know determine the effect of marketing strategies (service marketing mix) positively and significantly of customer interest. In this research used eight independent variables namely product, price, place, promotion, people, physical evidence, process, customer services and dependent variable namely customer interest. The research is quantitative research with the object is the bank’s regular customers who use other types of savings than batara saving product. The method used in sampling is purposive sampling. Questionnaire was used fot data collection. Data analysis techniques used respondents’ description analysis, variable description analysis, validity test, reliability test, multiple regression analysis and hypothesis testing. The results of research processed by computer application show that the R square value 0,524 means 52,4% customer interest is influenced by marketing strategies while the rest is 47,6% influenced by other variables not discussed in this research. The results of the simultaneous test or the F test show that the significance value of 0,000 F table 2,126. Based on the results of the research above, it can be concluded that partially using the T test, the variables that have a positive and significant effect on customer interest are the price and promotion. The variables that have a positive but not significant effect on customer interest are product, people, physical evidence, process, and customer services. The variables that has a negative effect on customer interest is place variable. While simultaneously has a positive and significant effect of customer interest. The suggestion in this research is to further increase the place variable as a negative variable and attention to the price and promotion variables as the most dominant variables affecting customer interest so that it can increase customer interest. Key words: marketing strategies, product, price, place, promotion, people, physical evidence, process, customer services and customer interest.